Predictive value of vitamin D levels in neonatal respiratory failure: a retrospective study - Zhang, Chenlu (Frontiers in Pediatrics, 2025)
ObjectiveTo retrospectively analyze the predictive value of an early neonatal vitamin D (vit D) level for neonatal respiratory failure in newborns.MethodsThe data of 220 hospitalized neonates, including 114 boys (51.8%) and 106 girls (48.2%), were collected from March 2021 to March 2023. Neonates were divided into respiratory failure (n = 52) and non-respiratory failure groups (n = 168) based on the respiratory status at the time of admission. Serum 25-hydroxy vitamin D [25(OH)D] levels were determined using a chemiluminescence immunoassay. The influence of serum 25(OH)D levels and perinatal factors on neonatal respiratory failure were analyzed. The predictive value of 25(OH)D for respiratory failure was evaluated.ResultsSerum 25(OH)D (OR = 0.896, 95% CI = 0.817–0.984) and birth weight (OR = 0.999, 95% CI = 0.998–1.000) were independent protective factors against neonatal respiratory failure, while gestational age < 34 weeks (OR = 8.293, 95% CI = 1.326–51.863) was an independent risk factor for neonatal respiratory failure (P < 0.05). The area under the receiver operating characteristic curve (AUC) for 25(OH)D alone was 0.620 (95% CI = 0.531-0.708). However, combining the 25(OH)D level with gestational age and birth weight improved the AUC to 0.868 (95% CI = 0.812-0.925) with a sensitivity of 0.750 and 1-specificity of 0.845 (P < 0.001).Conclusion25(OH)D deficiency may increase the risk of neonatal respiratory failure. Combining 25(OH)D with gestational age and birth weight was shown to have better predictive value for respiratory failure than serum 25(OH)D alone.